An Insight into the Dermatological Applications of Neem: A Review on Traditional and Modern Aspect - Singh, Varinder; Roy, Meghaditya; Garg, Nidhi; Kumar, Amit; Arora, Sandeep; Malik, Deepinder S. (Recent Advances in Anti-Infective Drug Discovery, 2021)
Background: Dermatological disorders are cutaneous infirmities which are frequently occurring and increasing at an alarming rate. These range from mild itching/redness (dermatitis) to fatal skin cancers and has posed a major health concern. Azadirachta indica A. Juss (commonly known as neem), a member of Meliaceae family, is an Indian medicinal plant which has been known for its health promoting effects since ancient times. Objective: The review highlights the traditional practices, pharmacological aspects, and formulatory approach of neem for the treatment of dermatological disorders. Further, recent patents and novel delivery systems (developed and in pipeline) improving skin delivery and therapeutic profile of neem are discussed. Results: Neem is a traditional medicinal plant that has been employed for the prevention and treatment of numerous ailments covering systemic and topical disorders. Scientific studies have validated the traditional claims of neem and attributed these health benefits to the presence of more than 300 structurally diverse and complex compounds. It possesses anti-inflammatory, antibacterial, analgesic, antiviral, antifungal, immunomodulatory and antioxidant activities which substantiate its use as skin therapy. Various novel formulations and associated patents that improved the permeability of neem based products across skin could be found in literature. Conclusion: Critical appraisal of available literature revealed that neem possesses anti-microbial, anti-inflammatory, antioxidant and antiseptic properties. Thus it has the potential to be developed as a single effective therapy for the management of multimodal skin disorders. Further, pharmaceutical tailoring of neem by implication of novel carriers could enhance its penetrability across skin.
Keywords: novel formulations